الحوار الأسري عند الشيخ علي يحيى معمر من خلال كتابه سمر أسرة مسلمة - فخار, حمو; الدبوز, سعيد (Sharwes Scientific Journal, 2024)
All Muslims agree that one of the foundations for building a strong Muslim family, which Islam is keen on, is the establishment of the Muslim family according to the principle of family dialogue, by raising its members on it from the beginning of the family, and so that its children grow up on it from the time they are born. This is what prompted Sheikh Ali Yahya Muammar to write his book, Summer of a Muslim Family, which made us search for During this intervention on the problem of the extent of the Sheikh’s success in establishing the method of family dialogue within the folds of his aforementioned book.To answer this problem, we divided our intervention into two axes, the first of which was to introduce Sheikh Ali Yahya Muammar and the second to present the Sheikh’s efforts to establish and highlight the controls and conditions for family dialogue through his book Summer, a Muslim Family. We concluded our intervention with a set of results and recommendations.